Functional Neuroimaging in Memory and Memory Disturbances - Reinhold, Nadine; Kuehnel, Sina; Brand, Matthias; Markowitsch, Hans J. (Current Medical Imaging, 2006)
During the past years brain imaging techniques like positron emission tomography (PET) and functional magnetic resonance imaging (fMRI) became more and more important for gaining new insights into processes of and circuits for memory encoding and retrieval. These findings also had a great impact on a better understanding of memory dysfunctions and their underlying brain mechanisms. In the present review, data on memory dysfunctions are analyzed separately according to whether they are of an organic, or a psychiatric psychogenic etiology. Studies examining patients with various forms of amnesia and dementia, for whom functional brain imaging data were available, indicate early functional brain changes. These early changes differ from subsequent structural brain changes and therefore support the clinical and diagnostic use of functional brain imaging techniques in memory disturbances. Furthermore, research outcomes from patients suffering from psychogenic amnesias (dissociative amnesias) and psychogenic fugue conditions are summarized. Finally, differences and similarities between organic amnesia and psychogenic amnesia are discussed with regard to the present literature and exemplified with two single cases from our lab.
Keywords: PET